Inhibition of Rheumatoid Arthritis Using Bark, Leaf, and Male Flower Extracts of Eucommia ulmoides. (13th August 2020) - Xing, Yun-Yun; Wang, Jian-Ying; Wang, Kai; Zhang, Yan; Liu, Kun; Chen, Xiao-Yun; Yuan, Ying
Abstract : Eucommia ulmoides Oliv., a native Chinese plant species, has been used as a traditional Chinese medicine formulation to treat rheumatoid arthritis (RA), strengthen bones and muscles, and lower blood pressure. Various parts of this plant such as the bark, leaves, and flowers have been found to have anti-inflammatory properties. E. ulmoides has potential applications as a therapeutic agent against bone disorders, which were investigated in this study. In vitro, RA joint fibroblast-like synoviocytes (RA-FLS) were treated with different concentrations (0, 25, 50, 100, 200, 400, 800, and 1000 μ g/mL) of E . ulmoides bark, leaf, and male flower alcoholic extracts (EB, EL, and EF, respectively) to determine their potential cytotoxicity. Tumor necrosis factor- (TNF-) α and nitric oxide (NO) levels in RA-FLS were quantified using enzyme-linked immunosorbent assay (ELISA). Furthermore, collagen-induced arthritis (CIA) rats were treated with EB, EL, EF, Tripterygium wilfordii polyglycoside (TG) or the normal control (Nor), and then ankle joint pathology, bone morphology, and serum and spleen inflammatory cytokine levels were evaluated. The results showed that, in RA-FLS, EB, EL, and EF were not cytotoxic; EB and EF reduced TNF- α supernatant levels; and EB, EL, and EF reduced NO levels. The results of in vivo experiments showed that EB, EL, and EF alleviated ankle swelling and joint inflammation, while all extracts diminished inflammatory cell infiltration, pannus and bone destruction, and bone erosion. All tested extracts inhibited interleukin- (IL-) 6, IL-17, and TNF- α mRNA in the spleen of CIA rats, while EB most effectively reduced osteoclasts and inhibited bone erosion. EF showed the most obvious inhibition of inflammatory factors and pannus. Thus, EB, EL, and EF may alleviate bone destruction by inhibiting inflammation.